STABILITY OF GPS AND GLONASS ONBOARD CLOCKS ON A MONTHLY BASIS - Michał ZIĘTALA (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents the stability of the GPS and GLONASS system clocks’ stability. It describes the construction of these two systems and calculated four different Allan variances (AVAR), based on the MGEX (the Multi-GNSS Experiment) clock products. Four used variances allowed making a better analysis of each GNSS system clock. The results are shown at different averaging times from 5 s as successive multiples to 655,360 s in a monthly period. The stability of GPS and GLONASS clocks is included in the range of 10-12~10-14 s. The results showed that GLONASS clocks are stable (10-12~10-14 s) and are affected with white frequency noise (WFM). The GPS clock stability models have more fluctuations for τ > 40,960 s and the mean stability is concluded between 10-12~10-13 s. Mean frequency accuracy for GPS clocks is related with WFM and Random Walk Frequency (RWF). The differences in clock stability are caused by several factors – block type, type of clock and the time of a satellite in orbit. These factors have an influence on stability results.